Impact of body-positive social media content on body image perception - Ana Maria Jiménez-García; Natalia Arias; Elena Picazo Hontanaya; Ana Sanz; Olivia García-Velasco (Journal of Eating Disorders)
Abstract Introduction Social media significantly impacts body image perception, particularly on visually driven platforms that propagate idealized, edited images. These platforms reinforce unrealistic beauty standards, contributing to body dissatisfaction and mental health issues such as anxiety and eating disorders. Movements like body positivity advocate for diverse body acceptance and challenge these ideals, yet questions remain about its long-term efficacy in reshaping body image perceptions and promoting psychological wellness. Methods A systematic review and meta-analysis were conducted following PRISMA guidelines, analyzing studies published until 2024 across PubMed, Scopus, ScienceDirect, and Web of Science. Fifty-six studies examining the effects of body-positive content on social media were reviewed, including experimental and observational designs addressing short- and long-term impacts. Nineteen studies were excluded from the meta-analysis due to unsuitable data or lack of control groups. Meta-analyses of effect sizes between experimental and control groups were performed using R software. Results The meta-analysis found that body-positive content improves body satisfaction and emotional well-being immediately, especially when highlighting diverse representations and self-acceptance. Longitudinal studies reported sustained improvements in body satisfaction with consistent exposure. Significant gains in body appreciation as a trait were observed, while state-based measures showed no significant effects. Variables like body dissatisfaction and functionality also lacked significant changes. Although body-positive content reduces some harmful effects of conventional beauty standards, its influence on body surveillance and social comparison remains limited. Study variability underscores the need for targeted approaches to optimize its impact on diverse populations. Discussion Body-positive social media content shows promise in improving body satisfaction, appreciation, and mood in the short term. However, further research is required to clarify its long-term effects, develop standardized assessment methods, and identify the most effective strategies for diverse demographic groups. This research is vital to fostering healthier, more inclusive body image perceptions in the digital age.